PERSPEKTIF MURTAD DALAM PERKAWINAN MENURUT HUKUM POSITIF ISLAM DAN FIKIH 4 IMAM MAZHAB - Efita Nurhidayati; Miftakhul Huda (Faculty of Law, Mahasaraswati University, Denpasar, 2025)
Apostasy before marriage only has an impact on the perpetrator, while apostasy in marriage has an impact on the family. Article 116 letter h of the Compilation of Islamic Law regarding apostasy in marriage is weak, so further discussion is needed. This research uses normative juridical methods with a statutory and conceptual approach, as well as primary, secondary, and tertiary data sources. The results of the study show a difference in perspective between Islamic positive law, namely Article 116 letter h of the Compilation of Islamic Law and Islamic jurisprudence related to apostasy in marriage, especially in terms of tolerance given. In addition, there is a conflict between similar articles and with conflicts with higher provisions